Soul, death and immortality - Casertano, Giovanni (Revista Archai, 2016)
Plato’s dialogues are great theatrical performances. These representations put into the scene something that none of the Greek tragedians or comedians dared to treat before Plato: philosophy. Each dialogue is therefore a play that deals with a topic, or many topics of philosophy, which makes Plato responsible for “philosophy” first meaning and connotation. The Phaedo was, of course, interpreted in many different ways. In the Phaedo, we do find a set of ideas opposed to a pure and simple empiricism; we do find the theory of the immortality of the soul; we do find logical and argumentative inconsistencies. However, in order to make sense of all that, we must stop seeing Phaedo as treatise on philosophy. Thus, Phaedo must be read as a theatrical work that brings into play a unique situation ”“ the last day of Socrates’ life ”“ with unique characters discussing philosophy, or, in other words, what is philosophy for them. And they argue ”“ and this is really what Plato puts into play ”“ with all the complexity of feelings that they sometimes experience: pleasure and pain, tears, smiles and laughter, groans and commotion. In this last day, in Socrates’ cell, a synthesis of all these men’s lives is shown.